Thị trường tiền tệ: nội dung cơ chế hoạt động và chính sách phát triển ở Cộng hòa XHCN Việt Nam - Vũ, Văn Hóa (2011)
Tác giả: Vũ Văn Hóa, PGS-PTS; Nguyễn Thị Mùi; Vũ Viết Ngoạn -- Từ khóa: Thị trường tiền tệ